Remarks on the Margin of Wojciech Włodarczyk’s Article “1989. On the Concept of Modernism” - Turowski, Andrzej (Artium Quaestiones, 2019)
A polemical response to Wojciech Włodarczyk’s article published in this issue of Artium Quaestiones